PENGATURAN HUKUM PENYELESAIAN KASUS KECELAKAAN LALU LINTAS SECARA DAMAI DALAM UNDANG UNDANG NOMOR 1 TAHUN 2023 - Barhamudin, Barhamudin; Bustomi, Abuyazid (Solusi, 2025)
The aim of this research is to find out how judges consider the arrangement between victims and perpetrators in traffic accident cases. This research aims to find out what factors are considered by the judge when imposing a sentence in this case. This research is normative legal research. The data used in this research consists of primary legal materials and secondary legal materials which are secondary data. Settlement of Peace between Victims and Perpetrators of Crime in the Criminal System In accordance with the development of modern criminal law, peace agreements between victims and perpetrators of crime are quite good. The forms of peace, the good intentions of the parties to make peace, are expressly stated in article 53 and article 54 of the New Criminal Code, namely in general sentencing guidelines for judges regarding matters that judges must consider in making a decision and mitigating factors in sentencing and provisions for forgiveness by victims as sentencing considerations for judges